Environmental Education Lesson Study: A Practical Analysis in Science Learning and Its Impact on Students’ Environmental Attitudes - Herlanti, Yanti; Fadlillah, Dina Rahma; Fadilah, Eva; Qumilaila, Qumilaila; Nobira, Shinji (FKIP Universitas Lampung, 2024)
Environmental Education Lesson Study: A Practical Analysis of Science Learning and Its Impact on Students' Environmental Attitudes. Objective: This study aimed to examine the implementation of an environmental education (EE) lesson study conducted by science teachers and to analyse its influence on students' environmental attitudes. Method: The methodology of research utilised a comprehensive approach that combined qualitative and quantitative from direct observations of the lesson study implementation in schools in the Serpong District from August 2023 to February 2024, a focused discussion group with six teachers, and environmental attitude online questionnaires with 406 students voluntarily participating in this survey. Finding: The findings indicate that the environmental education lesson study employs a framework of independent practice and open participation. While the planning and doing phases are managed independently by teachers from model schools, the observation and discussion phases actively involve educators from various schools, facilitating participation in hybrid formats. The students' environmental attitudes are not influenced by the activities of teachers within the lesson study. Instead, the type of school attended plays a critical role in shaping environmental attitudes. Students from eco-schools and those who prioritise environmental education as a distinct subject demonstrate considerably more positive environmental attitudes than those from institutions integrating environmental issues within their science learning. Conclusion: The environmental education lesson study has enhanced students' environmental attitudes. However, there is a need for a specific and holistic approach to environmental education to foster positive environmental attitudes among students effectively. Keywords: attitude, environmental, education, lesson study, science learning.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024134